Somatic Differentiation and MR Imaging of Magnetically Labeled Human Embryonic Stem Cells - Hossein Nejadnik; Tobias D. Henning; Rosalinda T. Castaneda; Sophie Boddington; Stefan Taubert; Priyanka Jha; Sidhartha Tavri; Daniel Golovko; Larry Ackerman; Reinhard Meier; Heike E. Daldrup-Link M.D., Ph.D. (Cell Transplantation, 2012)
Magnetic resonance (MR) imaging of superparamagnetic iron oxide (SPIO)-labeled stem cells offers a non-invasive evaluation of stem cell engraftment in host organs. Excessive cellular iron load from SPIO labeling, however, impairs stem cell differentiation. The purpose of this study was to magnetically label human embryonic stem cells (hESCs) via a reduced exposure protocol that maintains a significant MR signal and no significant impairment to cellular pluripotency or differentiation potential. hESCs were labeled by simple incubation with Food and Drug Administration-approved ferumoxides, using concentrations of 50–200 μg Fe/ml and incubation times of 3–24 h. The most reduced exposure labeling protocol that still provided a significant MR signal comparable to accepted labeling protocols was selected for subsequent studies. Labeled hESCs were compared to unlabeled controls for differences in pluripotency as studied by fluorescence staining for SSEA-1, SSEA-4, TRA-60, and TRA-81 and in differentiation capacity as studied by quantitative real-time PCR for hOCT4, hACTC1, hSOX1, and hAFP after differentiation into embryoid bodies (EBs). Subsequent MR and microscopy imaging were performed to evaluate for cellular iron distribution and long-term persistence of the label. An incubation concentration of 50 μg Fe/ml and incubation time of 3 h demonstrated a significantly reduced exposure protocol that yielded an intracellular iron uptake of 4.50 ± 0.27 pg, an iron content comparable to currently accepted SPIO labeling protocols. Labeled and unlabeled hESCs showed no difference in pluripotency or differentiation capacity. Ferumoxide-labeled hESCs demonstrated persistent MR contrast effects as embryoid bodies for 21 days. Electron microscopy confirmed persistent lysosomal storage of iron oxide particles in EBs up to 9 days, while additional microscopy confirmed the iron distribution within single and multiple EBs. Labeling hESCs with ferumoxides by this tailored protocol reduces exposure of cells to the labeling agent while allowing for long-term visualization with MR imaging and the retention of cellular pluripotency and differentiation potential.